1974
DOI: 10.1111/j.1445-5994.1974.tb03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Rheumatoid Arthritis in Schizophrenia*

Abstract: Summary: Middle‐aged women with a substantiated diagnosis of schizophrenia from Victorian Psychiatric Hospitals were examined for clinical, radiological and serological evidence of rheumatoid arthritis. Clinical or radiological evidence of rheumatoid arthritis was detected in none of the 301 patients studied, where‐as the expected prevalences would be 7.7%; this difference is highly significant (p < 0.001). On the other hand, the prevalence of serologically demonstrable rheumatoid factor in the women with sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Numerous studies including several tens of thousands of patients were identified (7,18,85,(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210)(211), the vast majority of which found a decreased frequency of rheumatoid arthritis among people with schizophrenia. Explanations may be of a genetic, environmental (institutionalization and sedentary lifestyle due to negative symptoms), pharmacological (analgesic and anti-inflammatory effects of antipsychotic drugs) and biochemical (histo-imcompatibility factors) nature [for review see (212,213)].…”
Section: Skin and Connective Tissue Diseases (392 Medline Hits)mentioning
confidence: 99%
“…Numerous studies including several tens of thousands of patients were identified (7,18,85,(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210)(211), the vast majority of which found a decreased frequency of rheumatoid arthritis among people with schizophrenia. Explanations may be of a genetic, environmental (institutionalization and sedentary lifestyle due to negative symptoms), pharmacological (analgesic and anti-inflammatory effects of antipsychotic drugs) and biochemical (histo-imcompatibility factors) nature [for review see (212,213)].…”
Section: Skin and Connective Tissue Diseases (392 Medline Hits)mentioning
confidence: 99%
“…Disturbances in carbohydrate metabolism and abnormalities of plasma and urinary glycoproteins have been reported in schizophrenia [6][7][8] and a very low incidence of carcinoma and rheumatoid arthritis has also been observed [9,10]. In this report, ·1,3FT activities were assayed in 44 patients with schizophrenia and in 50 healthy controls; 4 patients were found to be deficient in plasma ·1,3FT for the first time in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Acute exacerbations alternating with the psychosis have been reported. Mellsop et al (1974) cited 6 reports between 1939 and 1963 of the rarity of coincidence of the 2 conditions in the same individual. In their own study of 301 middle-aged schizophrenic women they found neither clinical nor radiological evidence of rheumatoid arthritis.…”
Section: Parkinson's Diseasementioning
confidence: 99%